The representation of source use in academic writing textbooks. (18th October 2021) - Sun, Qingyang; Soden, Bill
Abstract: Using sources appropriately is an important topic in teaching EAP. It involves a wide range of knowledge and skills, from the avoidance of plagiarism to the rhetorical attention to authorial stance and voice. Although a number of studies have shed light on how students cope with the challenges of source use, less is known about how each aspect is addressed in widely used EAP or study skills textbooks. This article presents an analysis of the representation of source use in thirteen concurrently used textbooks of academic writing. It was found that most of these textbooks discuss definitions of plagiarism and how to avoid it, with a fair number of textbooks also providing substantial activities on paraphrasing and summarizing. However, how citations can be used to take a stance and develop voice in academic texts is underrepresented. Implications for designing teaching materials and using textbooks in the classroom will be discussed.